Une approche ethnolinguistique sur le lexique de l’élevage chez les Jbala et les Ghomara (nord-ouest du Maroc) - Amina Naciri-Azzouz; Ángeles Vicente (Revue d'ethnoécologie)
Livestock is one of the activities of the traditional subsistence economy in the Jbala region. Nevertheless, socio-economic changes taking place in Northwestern Morocco are displacing this activity and along with it, the rich vocabulary related to it. This research discusses a small corpus of lexicon related to livestock gathered in situ with the peasants involved in this activity. We have focused on several interesting terms by providing a linguistic analysis and some ethnographical data.